Morphology and crystallographic phase of V–C particles formed in Fe–Cr–Ni–V–C alloys. (June 2013) - Takeda, M; Mitome, M; Hayakawa, H; Nishiuchi, S; Tanabe, T; Yamamoto, S
Abstract : The morphology and crystallographic phase of V–C carbide particles formed in cast Fe–Cr–Ni–V–C alloys were investigated by means of X-ray diffraction, scanning electron microscopy and transmission electron microscopy (TEM). The combination of results obtained with these techniques revealed that cuboidal, cruciform and spherical carbide particles were formed, depending on the alloy composition, all having the cubic-VC1−x structure (Fm-3m). Detailed TEM observations suggested that small carbide particles were initially cubic in shape and became spherical with increasing particle size. All cuboidal and spherical carbides were single crystallites with no grain boundary at any particle sizes, even after growing to 6 μm in diameter.